Energy Saving Behavior in Higher Education Institutions: A Bibliometric Analysis of Past and Future Research Trends - Alya Natasya; Gusman Nawanir (Universitas KH. Abdul Chalim Mojokerto, 2025)
This article aims to provide a comprehensive overview of the implementation of energy-saving behaviors in higher education institutions, highlighting past research trends and future challenges. This article uses a bibliometric approach involving 677 journal articles from the Web of Science. This study conducts co-citation and co-word analysis to map influential publications and predict trends. Past research trends on energy-saving behaviors have focused on cross-disciplinary approaches to create energy efficiency solutions, sustainability, and technology applications in various contexts, both households and buildings. In the future, research on energy-saving behaviors will increasingly focus on the integration of human behavior, technology, and design to support energy sustainability in facing global challenges. This article will benefit researchers and practitioners by improving their understanding and implementing energy-saving behaviors in higher education institutions. This article provides valuable practical implications for higher education institutions to achieve resource efficiency and support environmental sustainability. With a large student and staff population and high energy needs for campus operations, energy-saving behaviors can significantly reduce energy consumption and environmental impacts.